The effect of brand engagement on customer repurchase through customer value co-creation - Alireza Arab Armian; Mohammad Aghai; Fereshteh Mansouri Moayyed (کاوش‌های مدیریت بازرگانی, 2022)
Introduction: Understanding the importance of holding customers for organizations has led them to seek solutions. Today, marketing science is looking for ways to reciprocate mutual values between the customer and the organization, which is called value co-creation. Maintaining the customers is one of the most important factors that create mutual values for the ultimate enhancement of brands. So, it is better to get close to customers and meet their needs and expectations. This makes the relationship deeper; the customers become integrated with the brand, they participate in the process of creating value by partnership with the brand, and they ultimately receive a sense of value and come up with positive feedbacks. The purpose of this research is to investigate the effect of the level of brand engagement on customer repurchase through customer value co-creation. Therefore, in order to review repurchasing in this research, customer engagement with the brand is considered as a prerequisite for customer value co-creation. Also, three dimensions of the customer value, including pleasure, economic aspect and relationship, have been examined.Methodology: In this research, the dairy industry is considered as the case to study. The research population consisted of all the people who bought the local Chahar Fasl dairy brand in Shahrood more than once. This research is an applied type in terms of purpose and descriptive-survey in terms of data collection. By the Cochran formula, the sample size was determined to be 385. After a review of the related literature, a standard and appropriate questionnaire was prepared and distributed among the participants. Finally, 385 of the received responses could be analyzed. In order to analyze the collected data and test the hypotheses, the SPSS and Smart PLS software programs, the structural equation method and the confirmatory factor analysis were used. In general, the results of this research provide insight for brand managers and help them to know more about customers and the ways to build up loyalty in them, thus creating the desired value for them.Results and Discussion: The findings of the research are manifold. The first hypothesis examined the effect of customer engagement with the brand on the customer pleasure value. This hypothesis was confirmed with a path coefficient of 0.772. The second hypothesis was the effect of customer engagement with the brand on the customer economic value. It was also confirmed with a path coefficient of 0.595. The third hypothesis regarded the effect of customer engagement with the brand on the value of customer relationships value, which was also confirmed with a path coefficient above 0.903. The fourth hypothesis was about the effect of customer pleasure value on the customer repurchase. It was confirmed too with a path coefficient of 0.379. The fifth hypothesis addressed the effect of customer economic value on the customer repurchase, and this hypothesis was confirmed with a path coefficient of 0.321. The sixth hypothesis regarded the effect of the customer relationships value on the repurchase, which was also confirmed with a path coefficient of 0.215. Finally, the seventh hypothesis concerned the effect of customer engagement with the brand on customer repurchase. It was confirmed with a path coefficient of 0.712. The results of this study indicate that this brand has performed well in some aspects such as creating pleasure value and relationship value for customers. However, to make these values beneficial for customer repurchase, the brand has performed poorly and failed to persuade many customers to repurchase.Conclusion: Based on the results of the first, second and third hypotheses, brands should seek to better meet customer expectations, continue their relations with customers and gain a good place in their minds. They can increase customers' perception of receiving excitement and pleasure as well as provide cost and economic benefits and respectful and friendly relationships resulting from buying the brand. Also, based on the results of the fourth, fifth and sixth hypotheses, brands should be able to set up appropriate relations and partnerships with customers and create value for them by giving value to economic and pleasure relations and making the customers loyal to the brand. Thus, they may decide to repurchase the brand, which guarantees the success of the brand. Based on the results of the seventh hypothesis, brands should plan and implement the process of creating loyalty by engaging the customers so as to increase the likelihood of their return and re-purchases. In line with these results, practical suggestions have been made to increase customer repurchase.